Challenges in Managing Eyelid Basal Cell Carcinoma with Mohs Surgery and Close the Large Eyelid Defect after Tumor Removal - Rio Rhendy; Yunia Irawati; Adhimukti Sampurna (Majalah Oftalmologi Indonesia, 2015)
Background: Basal cell carcinoma (BCC) is the most common skin cancer of the eyelid. The important things management we have to emphasize are to prevent recurrence rate and to get the good cosmetic result after reconstruct the large defect. The aim of this case report is to show the management of both eyelid basal cell carcinoma and large eyelid defect after tumor removal.Methods: Case Report. A Woman 40 years old was reffered from Dermatovenereology Department of Cipto Mangunkusumo Hospital with aggressive type BCC. The location of the tumor was at inferior left eyelid with size of 18 x 19 mm. They planned to perform Mohs’ surgery and consulted to Plastic and Reconstruction division of Ophthalmology Department for eyelid reconstruction. After Mohs’ surgery the horizontal length of the eyelid defect was more than 50% and vertical defect was more than 15 mm. The Mustarde cheek advancement flap were choosen.Results: Post operation necrotic tissue was noted do to ischemic problem. Oral corticosteroid was given with tapering dose for six days. One month later, the condition was improved and Dermatovenereology department performed diode laser for the necrotic tissue and further showing good result.Conclusion: The management for eyelid BCC were still challenging including the technique to reconstruct the large eyelid defect, the risk of recurrence after the tumor removal and post operative result. The dicision to choose the proper technique to reconstruct the eyelid defect and tight follow-up after surgery will give optimal functional and cosmetic result. Keywords: basal cell carcinoma; Mohs surgery; Mustarde cheek advancement flap; necrotizing flap; corticosteroid; diode laser